Proteomics reveals the significance of vacuole Pi transporter in the adaptability of Brassica napus to Pi deprivation - Han, Bei; Yan, Junjun; Wu, Tao; Yang, Xinyu; Wang, Yajie; Ding, Guangda; Hammond, John; Wang, Chuang; Xu, Fangsen; Wang, Sheliang; Shi, Lei (Frontiers in Plant Science, 2024)
Vacuolar Pi transporters (VPTs) have recently been identified as important regulators of cellular Pi status in Arabidopsis thaliana and Oryza sativa. In the oil crop Brassica napus, BnA09PHT5;1a and BnC09PHT5;1a are two homologs of AtPHT5;1, the vacuolar Pi influx transporter in Arabidopsis. Here, we show that Pi deficiency induces the transcription of both homologs of PHT5;1a genes in B. napus leaves. Brassica PHT5;1a double mutants (DM) had smaller shoots and higher cellular Pi concentrations than wild-type (WT, Westar 10), suggesting the potential role of BnPHT5;1a in modulating cellular Pi status in B. napus. A proteomic analysis was performed to estimate the role of BnPHT5;1a in Pi fluctuation. Results show that Pi deprivation disturbs the abundance of proteins in the physiological processes involved in carbohydrate metabolism, response to stimulus and stress in B. napus, while disruption of BnPHT5;1a genes may exacerbate these processes. Besides, the processes of cell redox homeostasis, lipid metabolic and proton transmembrane transport are supposed to be unbalanced in BnPHT5;1a DM under the -Pi condition. Noteworthy, disruption of BnPHT5;1a genes severely alters the abundance of proteins related to ATP biosynthesis, and proton/inorganic cation transmembrane under normal Pi condition, which might contribute to B. napus growth limitations. Additionally, seven new protein markers of Pi homeostasis are identified in B. napus. Taken together, this study characterizes the important regulatory role of BnPHT5;1a genes as vacuolar Pi influx transporters in Pi homeostasis in B. napus.